Prawosławna ikona na przecięciu duchowych i politycznych dróg. Wybrane problemy - Zając, Marta (Przegląd Wschodnioeuropejski, 2024)
This paper is meant as a commentary on less obvious developments of Western and Eastern Christian spirituality. It can hardly be denied that religions have their connections with this world: history, geography, culture, and accordingly develop in symbiosis with their environment. The reverse of that is the influence which religious beliefs exert on cultural endeavours, a most spectacular example of which is the art of painting. In this vein, the author examines the political and cultural context of the partition into the Catholic and the Orthodox Christianity, together with the differences between Western and Eastern spirituality, to search then for the correspondences between the political and cultural formation and the modes of artistic expression. Finally, some possible connections are established between the politically and historically-shaped spiritual traits of the Catholic and Orthodox Church, and the rules which inspired Western religious painting and the writing of icons, respectively.